2023
DOI: 10.7759/cureus.49331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictive Factors of Cervical Cancer Screening in Saudi Arabia: A Nationwide Study

Fatimah H Alkhamis,
Zainab Alabbas S Alabbas,
Jwaher E Al Mulhim
et al.

Abstract: Background: Cervical cancer, despite being preventable, is one of the most prevalent cancers among females globally and in Saudi Arabia. The literature demonstrated that, unlike global trends, cervical cancer incidence in Saudi Arabia is increasing. In addition to that, a high proportion of it is discovered in advanced stages. This state of late discovery was attributed to the absence of efficient preventive and screening programs. Observing the scale of the preventable morbidities and mortalities that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Questions arise about the integration of cervical cancer prevention, such as HPV vaccination, into the healthcare system. A recent nationwide study in the KSA focused on sexually active Saudi women aged 21 to 65, revealing concerning trends in cervical cancer screening and HPV vaccine uptake [ 8 ]. The findings showed that only 22.1% of participants had undergone cervical cancer screening, with merely 7.6% receiving the HPV vaccine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions arise about the integration of cervical cancer prevention, such as HPV vaccination, into the healthcare system. A recent nationwide study in the KSA focused on sexually active Saudi women aged 21 to 65, revealing concerning trends in cervical cancer screening and HPV vaccine uptake [ 8 ]. The findings showed that only 22.1% of participants had undergone cervical cancer screening, with merely 7.6% receiving the HPV vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous barriers impede prevention, screening and treatment of cervical cancer, leading to a complex challenge for the healthcare system [ 7 ]. There exists multiple knowledge and research gaps, particularly in the realm of preventive efforts such as HPV vaccination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human papilloma virus (HPV) commonly causes benign oral squamous papillomas but high-risk strains have also been demonstrated in dysplastic lesions and is a separate risk factor for oropharyngeal cancer [ 70 ]. In the US, HPV is the leading cause of oropharyngeal carcinoma and accounted for 70% of all cases [ 71 ].…”
Section: Other Risk Factors For Oral Cancermentioning
confidence: 99%